Stylistics Analysis of The Poem “An Old Man’s Winter Night” by Robert Frost: English - Johanes Rhana Saputra; Fithriyah Inda Nur Abida (Hasanuddin University, 2021)
Stylistics analysis gives an impartial and scientific opinion based on solid quantifiable data and methodical application. It makes use of specific technical vocabulary and notions derived from linguistics. The four layers of language aspects that can be studied stylistically are phonology, graphology, grammar, and semantics. The purpose of this research is to examine the stylistic features of Robert Frost's poem